African Woman Rises from the Ashes: Alice Walker’s Mimicry of Classic Ethnography in Possessing the Secret of Joy - RAMIN, Zohreh; Nowrouzi ROSHNAVAND, Farshid (Anafora, 2023)
Before the advent of deconstructive schools of thought in the second half of the twentieth century, anthropology and ethnography were hailed as scientific disciplines whose major consideration was to provide an objective analysis of other cultures. However, the launch of such critical approaches as postcolonialism, feminism, and postmodernism has nullified the two disciplines’ claim to scientificity and objectivity by laying bare their sexist, racist backdrop. In the postist zeitgeist, new ethnographies have been promoted in an attempt to disrupt the hierarchical relationship between the researcher and the studied subject of classic ethnography through including first-hand marginalized voices. Moreover, they blur the long-held generic boundaries between science and fiction via establishing the “ethnographic novel” as a medium that committedly voices the subalterns. Alice Walker’s Possessing the Secret of Joy (1992) is one of these new ethnographic novels which has as its protagonist an oppressed African woman. What makes Walker’s work distinct and notable is that the feminist writer subversively employs the conventional mode of ethnographic writing to stand up to African patriarchy and its horrific ritual of female circumcision.